The Influence of Halal Label, BPOM Label, and Price on the Purchase Decision of Madame Gie Products - Hana Malvalia Andiya; Titik Kusmantini (UPN Veteran Yogyakarta, 2023)
The type of research that researchers conduct is quantitative research which aims to determine the effect of Halal Label, BPOM Label, and Price on Purchasing Decisions. The population used in this study were all customers of Madame Gie beauty products in Sleman, Yogyakarta. The sampling technique was carried out using purposive sampling so that a sample of 110 respondents was obtained. Data collection was carried out using a questionnaire. The analytical tool used is descriptive and quantitative methods using multiple linear regression analysis with the help of the SPSS 25 program. The results of this study concluded that Halal Label has a positive and significant effect on purchasing decisions, BPOM Label has a positive and significant effect on purchasing decisions, Price has a positive and significant effect on purchasing decisions, and Halal Label, BPOM Label, and Price together have a positive and significant effect on purchasing decisions. Keywords: Halal Label, BPOM Label, Price, Purchasing Decision